Countering and Preventing Terrorist Crimes in the Virtual Social Networks - Peyman Namamian (حقوق فناوریهای نوین)
Actions such as the publication of the mass killing of journalists and the arrest of a large number of nationals of countries joining terrorist organizations and groups confirm the growing spread of ideas and recruitment of human resources in social media by terrorists. The proliferation of terrorist organizations using social media creates new challenges for online platforms, policymakers, and governments. Additionally, the popularity of social media around the world provides a huge potential audience for framing terrorist action. Unfortunately, due to the non-cooperation of the governments, control measures and police surveillance of the Internet and consequently virtual social media have failed. Therefore, the use of social media by terrorist groups is a new challenge for anti-terrorist mechanisms. Therefore, to deal with and prevent terrorist crimes in cyberspace in the form of social networks, it is necessary for international organizations, especially the United Nations and affiliated institutions, while making legal policies, to call on governments to support this matter so that the possibility of violating international peace and security. Due to the movements of terrorist groups in social networks are suppressed and pursued through international forums